2009
DOI: 10.1111/j.1365-2869.2009.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

The sleep of children with attention deficit hyperactivity disorder on and off methylphenidate: a matched case-control study

Abstract: SUMMARYIn the present study, we assessed the effects of regular use of methylphenidate medication in children diagnosed with attention deficit hyperactivity disorder (ADHD) on sleep timing, duration and sleep architecture. Twenty-seven children aged 6-12 years meeting diagnostic criteria for Diagnostic and Statistical Manual version IV ADHD and 27 control children matched for age (±3 months) and gender. Two nights of standard polysomnographic (PSG) recordings were conducted. ADHD children were allocated random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…Methylphenidate delayed the onset of the main sleep bout at the beginning of the light period and reduced the amount of sleep over 24 h, matching findings reported in humans (Galland et al, 2010). Both effects were mainly found in NREM sleep whereas REM sleep was not changed significantly.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Methylphenidate delayed the onset of the main sleep bout at the beginning of the light period and reduced the amount of sleep over 24 h, matching findings reported in humans (Galland et al, 2010). Both effects were mainly found in NREM sleep whereas REM sleep was not changed significantly.…”
Section: Discussionsupporting
confidence: 74%
“…Some studies suggest that methylphenidate, a common pharmacotherapy for ADHD, may exacerbate these sleep problems (Corkum et al, 2008;Galland et al, 2010;Ironside et al, 2010;Sangal et al, 2006;Schwartz et al, 2004). We show here that in healthy adult mice, methylphenidate alone can alter both sleep and circadian rhythmicity.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Some have suggested that stimulant medication causes sleep disturbances in children and adolescents with ADHD. Some studies of stimulant medication have supported this, but others have shown no change or improvements in sleep in children and adolescents treated with psychostimulant medication, (Galland et al, 2010;Mick, 2000;Barkley et al, 1990;O'Brien, 2003;Kim, 2010;Giblin & Strobel, 2010).…”
Section: Medical Treatment For Adhd and Sleep Problems 71 Psychostimmentioning
confidence: 97%